James Wines, SITE and their Highrise of Homes How to ensure that a single project represents the union of the desire of the citizens and the intentions of the urban planners - Quintana De Juan, Marta (Abaton. Revista de figuración, representación e imágenes de la arquitectura, 2023)
The compact city requires high-rise buildings, but it is the dispersed city that has grown and triumphed in recent decades. The proposal of the architect James Wines in the eighties, his Highrise of Homes becomes relevant once again and unites the best of both worlds.